Leveraging Wage Subsidies to Facilitate Fair Wages and Increase Social Welfare - Tomer Blumkin; Haim Pinhas; Ro'i Zultan (Center for Economic Studies and ifo Institute (CESifo), 2017)
Wage subsidies can be provided directly to the worker, as in the federal Earned Income Tax Credit (EITC) program. They can also be provided indirectly by subsidizing the employer; by reducing the cost of labor, employers are induced to offer higher wages. The standard literature stipulates that the identity of the entity that is statutorily entitled for the subsidy bears no implications for the economic incidence. We propose and test a mechanism by which indirect subsidies can lead to higher social welfare. A substantial empirical literature establishes that workers reciprocate gifts in the form of higher wages with the gift of exerting higher effort. Thus, if a wage subsidy is implemented by indirectly subsidizing employers, employers face a lower cost of labor and increase their wages, leading workers to reciprocate with higher effort and productivity than achieved by providing the equivalent direct subsidy. A controlled laboratory experiment supports our behavioral hypotheses and confirms the behavioral and welfare implications
Keywords: C92; H21; H22; H53; J33; 330; wage subsidies; welfare; gift exchange; tax incidence